Identification of Quantitative Trait Loci for Popping Traits and Kernel Characteristics in Sorghum Grain. Issue 4 (18th May 2017) - Pugh, N. Ace; Rodriguez‐Herrera, Raul; Klein, Robert R.; Klein, Patricia E.; Rooney, William L.
Abstract : Popped grain sorghum [ Sorghum bicolor (L.) Moench] has developed a niche among specialty snack‐food consumers. In contrast with popcorn ( Zea mays L.), sorghum has not benefitted from persistent selective breeding for popping efficiency and kernel expansion ratio. Although recent studies have already demonstrated that popping characteristics are heritable in sorghum, the discovery of quantitative trait loci (QTL) for these traits could help expedite and streamline the breeding process. To that end, the objective of this study was to identify regions of the sorghum genome associated with kernel popping traits. Using digital genotyping technology in conjunction with linkage mapping methodology, QTL were identified for kernel popping efficiency and kernel expansion ratio. Additionally, sets of QTL were identified for desirable traits including kernel weight, kernel diameter, kernel hardness, and kernel color. These results provide an initial assessment of regions of the sorghum genome that harbor trait loci controlling the popping quality of sorghum kernels and provide a basis for further detailed genetic studies of this relatively new use for food‐grade sorghum grain.